Adult attachment orientations and psychopathology in clinical and non-clinical settings in Yemen : Rasch analysis and advanced structural equation modeling - Hafeeth, Naser Abdul (Kulliyyah of Education, Internatiional Islamic University Malaysia, 2014)
This study aimed at verifying the fitness of internalizing and externalizing forms of adult psychopathology, the evidences of the construct validity of MCMI-III (Millon, 1994) in clinical sample and the convergent validity of personality disorders model in non-clinical sample. Also, this study intended at verifying the universality, normativity and competence assumptions of attachment theory using clinical and non-clinical samples from non-Western culture (e.g., Yemen). Three assumptions reflect the validity of attachment theory in non-Western culture. The reciprocity of the attachment outcomes-psychopathology relationship was tested as an additional assumption to reflect validity of attachment theory in non-Western culture. While the MCMI-III was used to assess psychopathology in 212 outpatients and personality disorders in 300 undergraduate students, three self-report measures of adult attachment (RSQ, ECRS, and PAM) were used to assess the constructs of attachment theory including fearful, preoccupied, dismissing, and secure styles, anxiety and avoidance in interpersonal relationship and psychosis phenomena. Results of confirmatory factor analysis suggested that the MCMI-III with the two-factor model of psychopathology: internalizing and externalizing do fit the clinical data achieving good evidences for construct validity. An equivalent model on MCMI-III was explored and fit to the original model of internalizing and externalizing of psychopathology. Empirically, classification of psychopathology in terms of internalizing and externalizing is more useful than DSM-IV model; Axis II (Personality Disorders) and Axis I (Clinical Syndromes), which was characterized by comorbidity or overlap. The results of CFA indicated that MCMI-III was characterized by evidences of convergent and discriminant validity (construct validity) in clinical sample. The results of SEM confirmed the validity of the reciprocity of attachment styles-internalizing psychopathology relationship in clinical sample, suggesting that the large effect size of attachment styles on internalizing psychopathology in simultaneously latent test was less than the effect size of internalizing psychopathology on attachment styles. The results of invariant CFA confirmed that the hypothesized models of attachment theory do fit the data from clinical and non-clinical population (universality statement of attachment theory), demonstrating that the attachment models are more plausible in clinical than non-clinical populations (normativity assumption of attachment theory). The results of invariant SEM confirmed that the hypothesized models of attachment theory and personality disorders fit the data from clinical and non-clinical population (Competence assumption), suggesting that the attachment models and personality disorders are more plausible in clinical than non-clinical populations (competence assumption within the logic of normativity).